Managing Postoperative Pain in Orthopedic Patients: An International Comparison: Managing Postoperative Pain - Ayres, Jack M.; Dallman, Johnathan; Nolte, Jack A.; Higginbotham, Nicholas; Baker, Jordan; Horton, Greg; Salava, Jonathon; Sojka, John; Templeton, Kimberly; Malancea, Radu Ioan; Heddings, Archie (Kansas Journal of Medicine, 2023)
Introduction. Opioids play a crucial role in post-operative pain management in America, but not in some other countries. We sought to determine if a discrepancy in opioid use between the United States (U.S.) and Romania, a country that administers opioids in a conservative fashion, would show in subjective pain control differences.Methods. Between May 23, 2019, and November 23, 2019, 244 Romanian patients and 184 American patients underwent total hip arthroplasty or the surgical treatment of the following fractures: bimalleolar ankle, distal radius, femoral neck, intertrochanteric, and tibial-fibular. Opioid and non-opioid analgesic medication use and subjective pain scores during the first and second 24 hours after surgery were analyzed.Results. Subjective pain scores for the first 24 hours were higher among patients in Romania compared to the U.S. (p < 0.0001), but Romanians reported lower pain scores than U.S. patients in the second 24-hours (p < 0.0001). The quantity of opioids given to U.S. patients did not differ significantly based on sex (p = 0.4258) or age (p = 0.0975). However, females reported higher pain scores than male patients following the studied procedures (p = 0.0181). No sex-based differences in pain scores were noted among Romanian patients.Conclusions. Higher pain scores in American females, despite equivalent amounts of narcotics to their male counterparts, and the absence of a difference in Romanians suggested that the current American post-operative pain regimen may be tailored to the needs of male patients. In addition, it pointed to the impacts of gender, compared to sex, in pain experiences. Future research should look for the safest, most efficacious pain regimen suitable for all patients.